Room with trunks of families living in the Kudd - Mumbai Archive Project (Jio Institute, 2024)
The word kudd translates to room in the Konkani language, the native language of Goans. The Club of St. Anthony offers eight dormitories, six family rooms, three toilets, three common bathrooms, and a community kitchen. Once catering exclusively to young men, the Kudds have adapted to changing times. Nowadays, they are open to all, including women and families.